FLOW MATERIAL OPERATING USING DEVELOPED 3DIMENSIONAL DETECTOR IN STORAGE SYSTEMS (Perner's Contacts, 2009)
The issue on quantity of a material flow for assuring of continual material flow rate to sophistical material management of a logistic chain in general and response on material occurrence need change has been often investigated in the logistic system proposal. The paper deals with development and testing of developed 3Dimensional detector capable of identification of material flowage size especially to three-dimensional directions. Moreover, the detector is patented for industrial design and shape detector applications have been patented also for trouble-free applications to storage systems.
Keywords: 3Dimensional detector; storage system; material flow